Lymphedema after combination treatment of head and neck tumors - A. M. Stepanova; A. M. Merzlyakova; G. A. Tkachenko; S. O. Podvyaznikov (Опухоли головы и шеи)
Lymphedema of  the head and neck after combination treatment of tumors of  this localization is an important problem as it leads to functional disorders, including life-threatening, and significantly decreases the quality of life. Early start of treatment prevents complications at the stage of edema. Currently, complete decongestive therapy in combination with low-level laser therapy allows to abate lymphedema manifestations.